THE ROLE OF TECHNOLOGY IN ENHANCING LANGUAGE ACQUISITION: A COMPARATIVE STUDY OF DIGITAL TOOLS IN LANGUAGE LEARNING - Elena Vasilenko (Modern American Journals, 2025)
In recent years, the integration of technology into language learning has significantly transformed the way students acquire and practice new languages. Digital tools, such as language learning apps, online platforms, and interactive multimedia resources, have become central in modern language acquisition. This study explores the role of technology in enhancing language learning by conducting a comparative analysis of popular digital tools. We focus on assessing the effectiveness of tools like Duolingo, Babbel, and Memrise in fostering language proficiency across different skill levels. Using a mixed-methods approach, we analyze user engagement, linguistic improvements, and learner satisfaction. Our findings reveal that while digital tools can enhance vocabulary retention, grammar comprehension, and speaking skills, the most effective tools integrate personalized learning pathways, real-time feedback, and social interaction components. This paper argues that the future of language education lies in a balanced integration of traditional and technological methods to create more interactive, adaptive, and accessible language learning environments.
Keywords: Language Acquisition, Technology in Education, Digital Tools, Language Learning Apps, Pedagogical Innovation, Vocabulary Retention, Interactive Learning, Online Education